Rancang Bangun Sistem Monitoring dan Sortir Telur Konsumsi dengan Konveyor di Pabrik Telur Karangploso - El Chandra Theo; Moh. Abdullah Anshori; Martono Dwi Atmadja (Politeknik Negeri Malang, 2020)
So far, there are many manual methods used to determine the freshness of chicken eggs, for example utilizing sunlight or a flashlight to illuminate the eggs in a dark place and then look at the contents of the chicken eggs for sorting. The same process has also been carried out by breeders or grocery traders to sort chicken eggs based on their quality. The purpose of this research is to make a chicken egg detection device using a conveyor, LDR (Light Dependent Resistor) sensor, lamp, LCD (Liquid Crystal Display), servo motor, esp8266 module and Arduino Mega Microcontroller as a processor. The performance results of this device affect the condition of the egg chicken to be detected. The results of this study, this tool has an accuracy of 95% in detecting egg quality, where the LDR sensor shows an ADC value of <260 for indicators of good egg quality, while ADC values ??of more than> 26 for indicators of poor egg quality. Once the eggs are detected, the servo will direct good quality chicken eggs to the right and poor quality chicken eggs to the left. Delivery of notifications and information to the website application is done online and in real time, and a good internet network is required. The time it takes for the system to transmit data from the time the system detects an egg until it appears on the website is 20 - 50 ms, according to ITU-T standards